Webinar on Improving Understanding of IFRS-Based Sustainability Reporting Standards for Undergraduate and Postgraduate Accounting Lecturers, Students, and Practitioners: Webinar Peningkatan Pemahaman Standar Pelaporan Keberlanjutan berbasis IFRS S1 dan S2 bagi Dosen, Mahasiswa dan Praktisi Akuntansi - Kusuma Dewi; Udi Pramiudi; Dwi Maulina; Iriyadi Iriyadi; Sudradjat Sudradjat (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The increasing demand for transparency, accountability, and the integration of sustainability aspects in financial reporting has accelerated the global adoption of IFRS standards, particularly IFRS S1 and IFRS S2 developed by the International Sustainability Standards Board (ISSB). These standards emphasize the disclosure of financially relevant sustainability information, including climate-related risks and opportunities, to support long-term economic decision-making. This Community Service Program (PkM) aimed to enhance the understanding, readiness for adoption, and interest of students, lecturers, and accounting practitioners in implementing IFRS S1 and IFRS S2 through a webinar-based socialization program. The method involved the delivery of materials by experienced sustainability reporting professionals and the evaluation of program effectiveness using pretest and posttest questionnaires. The webinar was conducted online and involved participants from various regions across Indonesia. The results indicate an increase in the average scores across all indicators, including understanding of the standards, perception of the importance of IFRS S1 and S2 for career development, readiness for adoption, and interest in sustainability reporting topics. These findings suggest that online socialization is an effective approach to strengthening participants’ literacy and capacity regarding sustainability reporting standards. This activity is expected to contribute to improving the preparedness of human resources and institutions in implementing IFRS S1 and IFRS S2 in a sustainable, transparent, and globally aligned manner.